Optical properties of white organic light-emitting devices fabricated utilizing a mixed CaAl12O19:Mn4+ and Y3Al5O12:Ce3+ color conversion layer - Jeong, H S; Kim, S H; Lee, K S; Jeong, J M; Yoo, T W; Kwon, M S; Yoo, K H; Kim, T W (Journal of nanoscience and nanotechnology, 2013)
White organic light-emitting devices (OLEDs) were fabricated by combining a blue OLED with a color conversion layer made of mixed Y3Al5O12:Ce3+ green and Ca2AlO19:Mn4+ red phosphors. The X-ray diffraction patterns showed that Ce3+ ions in the Y3Al5O12:Ce3+ phosphors completely substituted for the Y3+ ions and the Mn4+ ions in the CaAl12O19:Mn4+ phosphors completely substituted for the Ca2+ ions. Electroluminescence spectra at 11 V for the OLEDs fabricated utilizing a color conversion layer showed that the Commission Internationale de l'Eclairage coordinates for the Y3Al5O12:Ce3+ and CaAl12O19:Mn4+ phosphors mixed at the ratio of 1:5 and 1:10 were (0.31, 0.34) and (0.32, 0.37), respectively, indicative of a good white color.